Determinan Human Capital dan Gender Direksi Terhadap Kinerja Perbankan di Indonesia - Yuliana Yuliana; Indra Widjaja (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study was to determine the determinants of the performance of banking companies in Indonesia. It is very important for a company to manage its Intellectual Capital through Human Resources (HR), Structural and whether the quality is managed in accordance with the principles of Good Governance, so as to improve company performance (Firm Size). The dependent variable is the Average Employee Age (Um), Average Employee Education (Pend), Employee Gender Composition (GenCom), Diversity of Female Directors (GenDir), Composition of Directors to Commissioners (DirCom), Number of Company Branches (Cab), Number of Employees (Kary). Samples are 11 banking companies on the Indonesia Stock Exchange which are classified as Book III and Book IV banks that publish annual reports and financial reports for 2015-2018. A total of 44 samples.Data were analyzed using linear regression test using SPSS. The results of the study for Intellectual Capital only (Cab) and (Kary) who have a significant influence, while (Um) and (Pend) do not have a significant effect. The results for Good Governance are the (GenCom) and (DirCom) significantly influence the performance, while (GenDir) has no significant effect. In a beta test (Kary) is the variable that most influences company performance.